Nos assombros cruéis da América Latina: o fantástico e as tensões sociais nos contos de Mariana Enriquez e Samanta Schweblin - Joana Gonçalves Coelho Silva (2025)
To undertake the task of thinking about the fantastic is to inquiry: what is the fantastic, anyway? According to David Roas (2014), it concerns the inexplicability of phenomena in narratives. In Remo Ceserani's view (2006), it is a literary mode that provokes disquiet in the reader's mind. Distancing itself from ghosts, vampires and other traditional creatures, to a certain extent, the contemporary fantastic – or neo-fantastic, in Alazraki's terms (2001) – presents in itself new characteristics. Within this context, the aim of this research was to reflect on the fantastic in contemporary literary works. Considering the fruitful development of this type of literature in Argentina, as well as the history of erasure of women writers from the literary canon, we chose as our object of study the work of two authors from Buenos Aires: Mariana Enriquez and Samanta Schweblin. Among Enriquez's narratives, we selected the short stories “La casa de Adela” and “Las cosas que perdimos en el fuego”, included in the homonymous collection Las cosas que perdimos en el fuego, released in 2016, as well as “Los himnos de las hienas”, from Un lugar soleado para gente sombría (2024). Among Schweblin's texts, we selected “Mujeres desesperadas” and “La pesada valija de Benavides”, both originally published in the collection El núcleo del disturbio (2002), and “Pájaros en la boca”, from the collection of the same title, published in 2008. This research also aimed to address the social tensions evoked by the narratives, such as the high rates of femicide and the exploitation of women, animals and the environment. In order to do this, we based our study mainly on feminist criticism, as well as reflecting on the history of violence and exploitation in Argentine territory, drawing on theorists such as Gerda Lerner (2019), Silvia Federici (2017), Carol J. Adams (2018), Valeska Zanello (2018), Nicolas Shumway (2008), Amalia Leguizamón (2023), John Berger (2021), Maria Esther Maciel (2023), among others. The analysis revealed how the works of Enriquez and Schweblin engage with social issues, so that the fantastic in their narratives unveils real horrors of everyday life. Despite the similarities, significant differences were found: while Enriquez approaches horror/terror, incorporating its elements and dialoguing with Gothic roots, Schweblin's delves into the restlessness characteristic of the neo-fantastic, exploring the limits between the possible and the impossible.